Ophthalmic artery Doppler at 11–13 weeks' gestation in prediction of pre‐eclampsia. (1st June 2022) - Gana, N.; Sarno, M.; Vieira, N.; Wright, A.; Charakida, M.; Nicolaides, K. H.
ABSTRACT: Objectives: To examine the potential value of maternal ophthalmic artery Doppler at 11–13 weeks' gestation, alone and in combination with the established first‐trimester biomarkers of pre‐eclampsia (PE), including uterine artery pulsatility index (UtA‐PI), mean arterial pressure (MAP), serum placental growth factor (PlGF) and serum pregnancy‐associated plasma protein‐A (PAPP‐A), in the prediction of subsequent development of PE. Methods: This was a prospective observational study in women attending for a routine hospital visit at 11 + 0 to 13 + 6 weeks' gestation. This visit included recording of maternal demographic characteristics and medical history, ultrasound examination for fetal anatomy and growth, assessment of flow velocity waveforms from the maternal ophthalmic arteries and calculation of the second‐to‐first peak systolic velocity (PSV) ratio, and measurement of MAP and serum PAPP‐A. In addition, a case–control study was carried out for measurement of PlGF in stored samples from cases that developed PE and unaffected controls. The values of PSV ratio, UtA‐PI, MAP, PAPP‐A and PlGF were converted to multiples of the median or deltas to remove the effects of maternal characteristics and medical history. The competing‐risks model was used to estimate the individual patient‐specific risk of delivery with PE at < 37 and < 41 + 3 weeks' gestation for various combinations of markers. Performance was assessed using detection rates, at a fixed false‐positive rate (FPR), and areas under the receiver‐operating‐characteristics curves. Modeled performance was also assessed. Results: The study population of 4066 pregnancies contained 114 (2.8%) that developed PE, including 25 (0.6%) that delivered with PE at < 37 weeks' gestation. The PSV ratio was significantly increased in PE pregnancies, and the effect of PE depended on gestational age at delivery, with the deviation from normal being greater for early than for late PE. Modeling demonstrated that the addition of PSV ratio improved the detection rate, at a 10% FPR, of preterm PE provided by maternal risk factors alone (from 46.3% to 58.4%), maternal factors, MAP and UtA‐PI (65.9% to 70.6%), and maternal factors, MAP, UtA‐PI and PlGF (74.6% to 76.7%). The PSV ratio did not improve the prediction of term PE provided by any combination of biomarkers. Conclusion: Ophthalmic artery PSV ratio at 11−13 weeks' gestation is a potentially useful biomarker for prediction of subsequent development of preterm PE, but larger studies are needed to validate this finding. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.